(untitled) (CIPEEX, 2024)
THE CONCEPT OF SELF-CARE IS THEMATIZED BASED ON FOUCAULT’S HERMENEUTICS OF THE SUBJECT (2014)AND DEWEY’S DEMOCRACY AND EDUCATION (1994), IN ORDER TO FORGE SUBSIDIES CAPABLE OFELUCIDATING THE IMPORTANCE OF SUCH A CONCEPT IN THE CONSTITUTION OF PROCESSES FORMATIONS ANDTHE COMMON HUMAN WORLD ITSELF. IT STARTS FROM THE PERSPECTIVE OF FOUCAULT’S NOTION OF SELF-CARE,IN ORDER TO UNDERSTAND HOW THE REPOSITIONING OF THE PROBLEM OF THE PHILOSOPHICAL PROBLEM OFKNOWING YOURSELF IS TAKEN AS SELF-CARE. FURTHERMORE, IT IS CONSIDERED THAT THE THEORIZATIONS OFJOHN DEWEY’S EDUCATIONAL PROJECT REMAIN EXTREMELY CURRENT, ESPECIALLY AT A TIME WHEN WEWITNESS THE EMPTYING OF THE FORMATIVE MEANING OF THE SUBJECT, AND THE HEAVY EMPHASIS ONDISCOURSES OF RESULTS AND PURPOSES. IN FOUCAULT, WE CAN SAY THAT THESE ARE THE TWOCHARACTERISTICS OF THE INSTRUCTIO: THE FORMATIVE AND THE CORRECTIVE ELEMENT; IN DEWEY, IT’S ABOUTLEARNING FROM EXPERIENCE, AND REORGANIZING IT, CORRECTIVELY, AS A CONTINUUM. SINCE EDUCATION ISINSTRUCTIONAL, IT HAS THE FORMATIVE AND CORRECTIVE SENSE, AND THIS ECHOES THE SENSE OF EDUCATIONAS A REORGANIZATION OF EXPERIENCE AS A CARE OF THE SELF, A CARE THAT MAKES THE SUBJECT IN HISFORMATIVE PROCESS AND EXPERIENCES CAN CONTINUOUSLY FACE LIFE, IN ADDITION TO BRINGING UPREASONS TO GOVERN HIMSELF THROUGHOUT HIS FORMATIVE PROCESS.